Prefrontal alterations in GABAergic and glutamatergic gene expression in relation to depression and suicide. (July 2018) - Zhao, J.; Verwer, R.W.H.; Gao, S.-F.; Qi, X.-R.; Lucassen, P.J.; Kessels, H.W.; Swaab, D.F.
Abstract: People that committed suicide were reported to have enhanced levels of gene transcripts for synaptic proteins in their prefrontal cortex (PFC). Given the close association of suicide with major depressive disorder (MDD), we here assessed whether these changes are related to suicide or rather to depression per se. We used quantitative PCR to determine mRNA levels of 32 genes encoding for proteins directly involved in glutamatergic or GABAergic synaptic transmission in postmortem samples of the anterior cingulate cortex (ACC) and the dorsolateral PFC (DLPFC). Seventy-two brain samples from 3 groups of subjects were derived from the Stanley Medical Research Institute (SMRI): i) patients with MDD who committed suicide (MDD-S), ii) MDD patients who died of non-suicidal causes (MDD-NS) and iii) age-matched, non-psychiatric control subjects. In the ACC, a significantly enhanced expression of genes related to glutamatergic or GABAergic synaptic transmission was found only in MDD-S patients, whereas in MDD-NS patients, decreased levels for these transcripts were found. Moreover, in the DLPFC, expression of these genes was decreased in MDD-S, relative to MDD-NS patients, whereas both groups showed increased expression compared to control subjects. In conclusion, our findings indicate that MDD is associated with increases in GABA and glutamate related genes in the DLPFC (irrespective of suicide), while in the ACC, the increase in GABA and glutamate related genes may relate to suicide, rather than to MDD per se.